Preparation of Polypropylene/Bentonite Composites of Enhanced Thermal and Mechanical Properties using L-leucine and Stearic Acid as Coupling Agents - Mohammedi, N.; Zoukrami, F.; Haddaoui, N. (Engineering, Technology & Applied Science Research, 2021)
The compatibilization of raw bentonite (bent) with a polymer matrix of polypropylene (PP) can improve the performance of the material in terms of thermal and mechanical properties. In this study, two kinds of untreated bentonite, bentonite-Maghnia (bent-m) and bentonite-Mostaganem (bent-M), that differ in the proportion of Al2O3 and in the particle size distribution were coupled to typical maleic anhydride grafted polypropylene PP-MA. Stearic Acid (SA) and L-leucine Amino Acid (AA) were selected as new coupling modifiers at a 5/5 ratio of bentonite/coupling agent. All PP/bent composites were prepared by melt mixing at 190°C. Morphological observation revealed a good dispersion of bentonite into the PP matrix in the presence of AA, SA, and PP-MA. Mechanical properties showed an increase in stiffness as bent-m or bent-M were associated with AA. For instance, PP/bent-m/AA composite underwent an improvement of about 13% in Young’s modulus as compared to neat PP. On the other hand, the addition of SA into bent-m maintained stiffness and tensile strength at an acceptable level. An increase of around 40°C and 37% in the decomposition temperature and elongation at break was respectively observed for the PP/bent-m/SA composite. All coupled composites showed high degradation temperatures.